Dual translinear sinusoidal frequency doubler and full-wave rectifier - Surakampontorn, W.; Jutaviriya, S.; Apajinda, T. (My University, 1988)
In this article, an integrable circuit principle which can be employed to realize both a sinusoidal frequency doubler and a full-wave rectifier is presented. The realization method makes use of a dual translinear characteristic of bipolar junction transistors. Two implementation circuits are proposed and their performance are demonstrated by experimental results. © 1988 Taylor & Francis Group, LLC.